Optimalisasi Edukasi Keuangan: Sosialisasi Gemar Menabung Bagi Generasi Muda Desa Balassuka - Fajrina, Nurul; Husain, Firman (JURNAL TEPAT : Teknologi Terapan untuk Pengabdian Masyarakat, 2024)
The program Optimization of Financial Education: Promoting a Saving Habit among the Youth of Balassuka Village aims to enhance financial literacy among elementary and junior high school students. This initiative included delivering educational materials on the importance of saving, conducting creative activities to make piggy banks from recycled materials, and evaluating results through Pre-tests and post-tests. Data analysis revealed a significant improvement in students' understanding, with the average pre-test score of 68 increasing to 85 in the post-test, based on a Paired Sample T-Test with a significance value of < 0.001. These findings indicate the program's success in raising awareness about saving as a positive habit and a fundamental financial management skill. Furthermore, the program highlights the importance of structured financial literacy education as a foundation for preparing the younger generation to face future financial challenges. It is hoped that the program's sustainability will be supported by active roles from parents and teachers in encouraging students to maintain saving habits. This initiative is also expected to inspire similar programs in the future.